2009
DOI: 10.1124/jpet.109.156034
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Hyperalgesia via Supraspinal Mechanisms in Mice Lacking Glutamate Decarboxylase 65

Abstract: ␥-Aminobutyric acid, which is synthesized by two isoforms of glutamate decarboxylase (GAD), inhibits the transfer of nociceptive signals from primary afferent fibers to the central nervous system. However, the roles of a 65-kDa isoform of GAD (GAD65)-mediated GABA in nociceptive processing are less clear. This study tested whether partial reductions in GABAergic inhibitory tone by GAD65 gene knockout [GAD65(Ϫ/Ϫ)] would contribute to the regulation of pain threshold in mice. Experiments were performed on male w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 40 publications
5
34
4
Order By: Relevance
“…23 This was based on the observation that kainate did not lead to hypometabolism in a GAD65 knockout mouse model exhibiting impairments in tonic inhibition. 23,33 As alterations in tonic inhibition are expected to rely on changes in neuronal GABA release, a convulsive dose of kainate, which affects both neurons and astrocytes, is required to mediate an augmented tonic inhibition and the associated hypometabolism. Moreover, the effect of tonic inhibition appears to be dramatic, as it is able to override the substantial metabolic changes observed in astrocytes induced by the subconvulsive dose.…”
Section: Discussionmentioning
confidence: 99%
“…23 This was based on the observation that kainate did not lead to hypometabolism in a GAD65 knockout mouse model exhibiting impairments in tonic inhibition. 23,33 As alterations in tonic inhibition are expected to rely on changes in neuronal GABA release, a convulsive dose of kainate, which affects both neurons and astrocytes, is required to mediate an augmented tonic inhibition and the associated hypometabolism. Moreover, the effect of tonic inhibition appears to be dramatic, as it is able to override the substantial metabolic changes observed in astrocytes induced by the subconvulsive dose.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the report that in rat persistent inflammatory and neuropathic pain epigenetically suppresses gad65 activities in the NRM through HDACmediated histone hypoacetylation, resulting in impaired GABA synaptic inhibition. 36 In addition, gad65 knockout mice exhibit thermal hyperalgesia 17 and display exaggerated pain behavior in conjunction with an impaired GABA synaptic function in the brainstem neurons. 36 This may also explain, at least in part, that the use of an HDAC inhibitor such as valproic acid can reduce hyperalgesia resulting from induced adenomyosis in mice, 9,20 since HDAC inhibitors overwhelmingly increase gad65 activities, restore GABA synaptic function, and relieve the sensitized pain behavior.…”
Section: Discussionmentioning
confidence: 99%
“…16 Mice lacking GAD65 exhibit thermal hyperalgesia, suggesting that GAD65-mediated GABA synthesis plays a significant role in nociceptive processing via supraspinal mechanisms. 17 Indeed, supraspinal GABAergic inhibition, usually through modulation of specific GABA A receptor subtypes, plays an important role in neuronal hyperexcitability and spinal/supraspinal nociceptive neurons. 18,19 We have previously shown that mice with induced adenomyosis exhibit increased uterine hyperactivity, general hyperalgesia, and elevated plasma corticosterone levels.…”
Section: Introductionmentioning
confidence: 99%
“…Gad2 KO mice display sensitized pain behaviors, 27,36 through histone hypoacetylation-induced downregulation of Gad2. 27 Viral delivery of the Gad2 gene or histone hyperacetylation-induced upregulation of Gad2 inhibits pain.…”
mentioning
confidence: 99%